Factors influencing bank profitability in a developing economy: empirical evidence from Malaysia - Sufian, Fadzlan (Sage Publications, 2011)
The present article examines the determinants of bank profitability in a developing economy. Specifically working within the Malaysian financial sector, the analysis is confined to the universe of the domestic and foreign commercial banks operating in the Malaysian financial sector during the period 2000–04. The empirical findings suggest that Malaysian banks with a higher credit risk and a higher loan concentration exhibit lower profitability level. On the other hand, banks that have a higher level of capitalization, a higher proportion of income from non-interest sources, and high operational expenses tend to exhibit higher profitability level. The results suggest that economic growth has a negative effect on Malaysian banks’ profitability, while a higher inflation rate has a positive impact on Malaysian banks’ profitability.